2022
DOI: 10.3389/fphar.2022.952660
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review on disposition kinetics and dosage of oral administration of Andrographis paniculata, an alternative herbal medicine, in co-treatment of coronavirus disease

Abstract: Coronavirus disease 2019 (COVID-19) is a present global health crisis that is driving the investigation of alternative phytomedicines for antiviral purposes. The evidence suggests that Andrographis paniculata crude or extract is a promising candidate for treating symptoms of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This review aims to consolidate the available reports on the disposition kinetics of andrographolide, a main active component of A. paniculata. The second objective of this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…With new variants of coronavirus still possible, it is essential to prevent its spread, and there are currently no effective antiviral drugs targeting SARS-CoV 1 . This global health crisis has led people to explore the use of TCM as antiviral treatment 28 .…”
Section: Discussionmentioning
confidence: 99%
“…With new variants of coronavirus still possible, it is essential to prevent its spread, and there are currently no effective antiviral drugs targeting SARS-CoV 1 . This global health crisis has led people to explore the use of TCM as antiviral treatment 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Although oral A. paniculata tablets were absorbed via the GI tract in dogs, the information about the pharmacokinetics involved is currently lacking ( Xu et al, 2015 ). Furthermore, variations in bioavailability across studies beyond species variations may be related to the use of various forms of A. paniculata ( Loureiro Damasceno et al, 2022 ; Songvut et al, 2022 ). Andrographolide metabolism and clearance variations have been observed among species ( Panossian et al, 2000 ; Zhao et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, the doses and treatment period of A. paniculata supplementation were insufficient. Secondly, the pharmacokinetic variations among species and dosage forms of A. paniculata may impact the plasma concentrations of andrographolide, leading to variations in the pharmacological response ( Zhao et al, 2013 ; Loureiro Damasceno et al, 2022 ; Songvut et al, 2022 ). Lastly, the biomarkers we used were not sensitive enough to identify the changes in the etiology and complications of DM.…”
Section: Discussionmentioning
confidence: 99%
“…Second, its anti-inflammatory effects are related to the reduced expression of interleukin-6 and tumour necrosis factor-alpha (Zhu et al, 2021) which cause tissue damage. Third, it systemically distributes to various organs, including the lungs (Songvut et al, 2022). It was found that C-reactive protein, an inflammatory biomarker that is stimulated by interleukin-6, is related to the severity of COVID-19 (Mueller et al, 2020).…”
Section: Discussionmentioning
confidence: 99%